2008
DOI: 10.1002/anie.200703237
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Nucleoside Diphosphate Glycopyranoses

Abstract: Nucleoside diphosphate pyranoses 1 (NDP sugars; see Scheme 1) play a key role as glycosyl donors in the synthesis of oligo-and polysaccharides. [1,2] Moreover, they serve as precursors of deoxysugars, aminodeoxysugars, chainbranched sugars, uronic acids, as well as glycoconjugates. In biosynthetic pathways the energy-rich linkage between the C1 atom and the b-phosphate is cleaved, and thus the glycosyl part is enzymatically transferred to an oligosaccharide chain, releasing the nucleoside diphosphate (NDP) moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…We first prepared (β-d-glucopyranoside)-thymine (5) and (β-d-galactopyranoside)-thymine (9). This was again achieved by the Vorbrüggen one-pot method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We first prepared (β-d-glucopyranoside)-thymine (5) and (β-d-galactopyranoside)-thymine (9). This was again achieved by the Vorbrüggen one-pot method.…”
Section: Resultsmentioning
confidence: 99%
“…Mainly, the Ludwig method is used. [7][8][9][10][11][12][13] With this method the synthesis of nucleoside-5Ј-triphosphates (both natural and non-natural compounds) was accomplished in yields of up to 80 % starting from the cycloSal-compound (64 % starting from the nucleoside). This might explain the low yields that were obtained by this method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent notable exceptions to this, however, do exist 4n. q, 22 Nonetheless, the simple, reproducible, and modular coupling under ambient conditions within a few minutes in approximately equimolar amounts of donor and acceptor as described in this publication has been a long‐standing synthetic challenge. The sensitivity of the P‐anhydride forming reaction to a 30‐fold scale‐up has been analyzed in the case of ADP‐βS (0.6 g of starting material 9 instead of 20 mg; see the Supporting Information) and no loss of efficiency regarding yield or purity of ADP‐βS were observed.…”
Section: Discussionmentioning
confidence: 99%
“…After oxidation of intermediate 10 and hydrolysis of the trimetaphosphate, ATP, CTP,GTP,and UTP of high quality were obtained. [38] Meier et al [39] reported the application of substituted chlorophosphites (11,S cheme 5) for the preparation of cycloSal-nucleotides 12 from appropriately protectedn ucleosides 5. Cyclo-Sal-nucleotides 12 reactedu nder dry conditions with phosphate,p yrophosphate, and various phosphoromonoesters, thereby affording nucleosided i-and triphosphates, dinucleoside 5',5'-di, and tetraphosphates, within 3-5 h. After deprotection and purification, unnatural nucleoside di-and triphosphates 13 wereo btained in 40-80 %y ield (50-62 %y ield for dinucleoside di-or tetraphosphates 13).…”
Section: The Use Of Compounds Containingap àCl Bondmentioning
confidence: 99%